A New Computational Technique Design for EMHD Nanofluid Flow Over a Variable Thickness Surface With Variable Liquid Characteristics - Irfan, Muhammad; Farooq, Muhammad Asif; Iqra, Tousif (Frontiers in Physics, 2020)
The objective of this paper comprises two key aspects: to establish descriptive mathematical models for constant and variable fluid flows over a variable thickness sheet by inducting applied electric and magnetic fields, porosity, radiative heat transfer, and heat generation/absorption, and to seek their solution by constructing a novel numerical method, the Simplified Finite Difference Method (SFDM). We resort to similarity transformations to implicate partial differential equations (PDEs) into a set of ordinary differential equations (ODEs). Optimal results for a pair of ODEs obtained from SFDM are assessed by drawing a comparison with bvp4c and existing literature values. SFDM has been implemented in MATLAB for both constant and variable fluid properties. Tabulated numerical values of the skin friction coefficient and local Nusselt and Sherwood numbers are measured and analyzed against different parameters. The influence of distinct parameters on velocity, temperature, and nanoparticle volume fraction are explained in great detail via diagrams. The skin friction coefficient for variable fluid properties is greater than for constant fluid properties. However, the local Nusselt number is lower for variable fluid properties than with constant fluid properties. Surprisingly, high-precision computational results are achieved from the SFDM.